Orbital Inflammatory Complications of Crohn's Disease: A Rare Case Series. (16th February 2018) - Monaghan, Tanya M; Albanese, Giorgio; Kaye, Philip; Thomas, James D; Abercrombie, Lorraine C; Moran, Gordon W
Orbital inflammatory disease is a rare ophthalmic manifestation of Crohn's disease. Inflammation is characteristically nonspecific, involving one or multiple structures of the orbit. Mechanisms of disease and optimal methods of treatment are poorly understood. The aim of this report is to present 3 cases of orbital involvement in Crohn's disease. A retrospective case note review of patients with orbital inflammatory disease and Crohn's disease was performed at our academic center to determine the clinical, imaging, and histopathologic features of this condition and its relationship to intestinal Crohn's disease. Three patients were identified with orbital inflammatory manifestations complicating Crohn's disease. All patients described were women with active intestinal disease and had a history of treatment with immunosuppressive therapies. Similarities were observed in clinical presentations with variance noted in radiologic and histopathologic findings. In all cases, symptoms improved with oral corticosteroids or nonsteroidal drugs in combination with anti-tumor necrosis factor agents. Inflammatory bowel disease–related orbital complications are rare but potentially vision-threatening. It is important to consider mimics of orbital inflammatory disease such as systemic inflammatory disease, malignancy, congenital malformations, infection, and trauma when formulating a comprehensive differential diagnosis. Therapeutic intervention is directed toward preservation of vision and orbital function and reducing the acute inflammatory process. Corticosteroids are typically the initial treatment of choice for moderate-to-severe disease, although several classes of immunomodulatory agents have been variably useful in treating this condition. Heightened awareness and close cooperation between gastroenterologists and ophthalmologists are mandatory.